“Impact of health promotion practices on health-related quality of life (HRQoL) among geriatric population in Karachi, Pakistan” - Ambreen Merchant (BMC Public Health)
Abstract Background Demographic transition has resulted in increased life expectancy among older adults that will lead to the emergence of new illnesses, long-term impairments, and alterations in social attitudes. The need to prioritize actions for this population, with a focus on enhancing the quality of life, fostering autonomy and independence, and promoting active and healthy aging, has made health education for the elderly a topic of global interest due to current demographic and epidemiological changes. The purpose of the study is to assess the impact of health promotion on enhancing health-related quality of life among elderly people in Karachi, Pakistan. Study setting and design Data was collected at a Senior Citizen & Recreation center, located near the participants’ residence in Karachi, Pakistan. A well-structured generic HRQoL instrument (SF-36) short form was used because it has demonstrated strong reliability and validity among the elderly population, making it a suitable tool for assessing quality of life outcomes. Methods One-group pre-test and post-test interventional (Quasi-experimental) research design using a mixed method approach (Qualitative and Quantitative). Inferential statistics are drawn through paired sample t-test to compare the mean of pre-test HRQoL scores with post-test HRQoL scores. The qualitative analysis was made through a thematic categorical method. Results Revealed significant impact of health-promoting activities on 3 sub-scales of HRQoL. However, on other subscales of HRQoL, health-promoting interventions produced little impact. Conclusion Health promotion can play a significant role in improving health-related quality of life.